MODERN MIGRATION TRENDS AND SOME FEATURES OF MIGRATION REGULATION IN PORTUGAL (World Bulletin of Management and Law, 2024)
This article analyzes modern migration trends, the mechanisms and main aspects of migration regulation in Portugal and its compliance with the international standard. The latest important changes in the field of migration legislation in Portugal are also discussed. In addition, the National Action Plan for the implementation of the The Global Compact for Safe, Orderly and Regular Migration, approved by Portugal, was analyzed, and the goals and necessary measures in the implementation of this Plan were studied. Based on the experience of Portugal, proposals and recommendations for improving the legislation of the Republic of Uzbekistan are provided